PENGARUH DEBT TO ASSET RATIO (DAR) DAN DEBT TO EQUITY RATIO (DER) TERHADAP RETRUN ON ASSET (ROA) PADA PERUSAHAAN SUB SEKTOR SEMEN YANG TERDAFTAR DI BEI - Jumratin Jumratin; Nafisah Nurulrahmatiah, Nurul Huda (CV. ADIBA AISHA AMIRA, 2023)
This research aims to examine the influence of Debt To Asset Ratio (DAR) and Debt To Equity Ratio (DER) on Return On Asset (ROA). The sample used in this study consists of financial data from 4 companies in the cement sub-sector over 4 years, from 2017 to 2021. The sampling method employed in this research is purposive sampling. The data were processed using SPSS with analytical techniques. The method of data analysis used is multiple linear regression, with partial and simultaneous hypothesis testing. The results of this study indicate that DAR does not have a significant effect on ROA, as the calculated t-value is -0.246 < t-table value of 2.110. Similarly, DER does not significantly affect ROA, as the calculated t-value is -0.103 < t-table value of 2.110. The simultaneous results show that both DAR and DER do not significantly affect ROA, with the calculated f-value of 0.346 < f-table value of 3.59